2006
DOI: 10.1016/s0022-5347(05)00005-4
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-Emodin Induces Apoptosis in T24 Human Bladder Cancer Cells Through the p53 Dependent Apoptotic Pathway

Abstract: AE induced apoptosis in T24 cells is mediated through the activation of p53, p21, Fas/APO-1, Bax and caspase-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 14 publications
3
63
0
2
Order By: Relevance
“…In anticancer researchs, overexpression of p53 is invovled in apoptosis inducted by many natrual anticancer agents (Lin et al, 2006;Hassan et al, 2013;Rengarajan et al, 2014). It has been well demonstrated that p53 could mediate transcriptional activation of Bax and trigger mitochondrial apoptosis (Toshiyuki et al, 1995;Chipuk et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In anticancer researchs, overexpression of p53 is invovled in apoptosis inducted by many natrual anticancer agents (Lin et al, 2006;Hassan et al, 2013;Rengarajan et al, 2014). It has been well demonstrated that p53 could mediate transcriptional activation of Bax and trigger mitochondrial apoptosis (Toshiyuki et al, 1995;Chipuk et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The isolated cells from each treatment were lysed individually and the total protein levels were quantified. To determine the proteins levels associated with invasion and migration (Ras, GRB2, MEKK3, FAK, MKK7, JNK, ERK, MMP-9, MMP-2, Rho A, PI3K, PKC, VEGF and c-jun-p) in N18 cells, all samples were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) as described previously (11,26,27).…”
Section: Methodsmentioning
confidence: 99%
“…N18 cells (1x10 6 /wells) in DMEM medium were plated onto 6-well plates and then were treated with 15 μM curcumin for 24 and 48 h. Cells were isolated from each treatment and the total RNA was extracted using the Qiagen RNeasy mini kit as described previously (27)(28)(29). All RNA samples were reversetranscribed individually for 30 min at 42˚C with high capacity cDNA Reverse transcription kit according to the standard protocol of the supplier (Applied Biosystems).…”
Section: Real-time Pcr Of Mmp-2 Mmp-7 Fak Rho a And Rock1mentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of AE on the activity and gene expression of N-acetyl transferase, which plays an initial role in the metabolism of aryl amine carcinogens, was found in human malignant melanoma cells [28]. Recently, Lin et al found that AE-induced apoptosis in T24 human bladder cancer cells was mediated through the activation of p53, p21, Fas/Apo-1, Bax, and caspase 3 [27]. Even if it was found through the work of Lee et al and Pecere et al that AE induces apoptosis in many cancer cells by increasing the concentration of Bax and by decreasing the concentrations of Bcl-2 [25,43].…”
Section: Introductionmentioning
confidence: 99%